Distinct Stress‐Dependent Signatures of Cellular and Extracellular tRNA‐Derived Small RNAs (Adv. Sci. 17/2022). Issue 17 (13th June 2022) - Li, Guoping; Manning, Aidan C.; Bagi, Alex; Yang, Xinyu; Gokulnath, Priyanka; Spanos, Michail; Howard, Jonathan; Chan, Patricia P.; Sweeney, Thadryan; Kitchen, Robert; Li, Haobo; Laurent, Brice D.; et al.
Abstract : Extracellular tRNA‐Derived Small RNAs In article number 2200829, Saumya Das and co‐workers provide a comprehensive landscape for the signature of cellular and extracellular tRNA‐derived small RNAs (tDRs) in response to different stressors. They also determine a distinct fragmentation pattern for extracellular tDRs distinct from cellular tDRs and investigate the basis of their biogenesis and stability.